A novel frameshift STAG1 variant exhibiting haploinsufficiency due to the nonsense-mediated mRNA decay: a case report and literature review - Jiang, Cuicui; Wu, Ke; Zhou, Ying (Frontiers in Pediatrics, 2025)
BackgroundThe heterozygous STAG1 gene (OMIM*604358) variants are associated with autosomal dominant intellectual developmental disorder 47, known as mental retardation autosomal dominant 47 (MRD47, OMIM#617635). Although more than 10 STAG1 variants have been reported, functional studies in vitro have not been performed. Our functional studies of a novel frameshift STAG1 variant in a Chinese boy have provided preliminary evidence confirming that the underlying pathogenic mechanism of MRD47 may be associated with STAG1 haploinsufficiency.MethodsTrio-based whole-exome sequencing (trio-WES) was performed on genomic DNA (gDNA) of peripheral blood samples from the boy and his parents. Mutant STAG1 expression vectors pcDNA3.1(+)-FLAG-STAG1-mut and control pcDNA3.1(+)-FLAG-STAG1-WT mammalian expression vectors were constructed. Both vectors were transformed into HEK293T cells. The assays of relative STAG1 gene mRNA expression and STAG1 protein expression were adopted.ResultsTrio-WES identified a novel heterozygous frameshift STAG1 gene variant (NM_005862.3) c.500dup (p.Gly168TrpfsTer13). Our in vitro functional findings revealed that this variant resulted in a dramatic reduction in the formation of STAG1 protein due to the decay of mutant STAG1 mRNA. The underlying pathogenic mechanism of MRD47 may be related to STAG1 haploinsufficiency.ConclusionMRD47 exhibits non-specific characteristics and diverse clinical phenotypes. Our functional studies have provided preliminary evidence confirming the haploinsufficiency of the STAG1 gene as the underlying pathogenic mechanism of MRD47. This study also expanded the mutational spectrum of the STAG1 gene and the clinical spectrum of MRD47.